Application of the Profile Matching Analysis Method in Decision Support Systems for Study Program Recommendations - Rasyada, Reza Dian; Nurdin, Nurdin; Fajriana, Fajriana (Sistemasi: Jurnal Sistem Informasi, 2024)
Currently, many prospective students are still confused about which study program to choose. One of the problematic factors is the lack of references from prospective students about the contents of each study program. This research aims to build a decision support system for study program recommendations using the Profile Matching Analysis method. The benefits of this research can provide final results in the form of recommended study program scores that are most suitable for prospective students. There are 5 assessment criteria used in this research, namely Language Values, Logic/IT Values, Science Values, Practice Values, and Social Values. The methods or stages carried out in this research are: data collection, system flowchart design, application of the Profile Matching Analysis method and system implementation. In this research, the recommendation results were obtained for a student with the name Afni Ruhmini based on the results of system calculations using the Profile Matching Analysis method, obtaining recommendation results for the Public Administration study program with a score = 5.3, the Marine Science study program with a score = 5.9, and the Agribusiness study program with a score = 5.6, the Physics Education study program with a score = 5.7 and the Law study program with a score = 4.8. The Profile Matching Analysis method is very suitable to be applied to solve problems in decision support system research for study program recommendations.